Acculturation, vitality, and bilingual healthcare - Bourhis, Richard Y.; Montreuil, Annie (The Oxford handbook of acculturation and health, 2017)
Chapter: 4

Talk COVID to me: Language rights and canadian government responses to the pandemic - Chouinard, Stéphanie; Normand, Martin (Canadian Journal of Political Science, 2020)
Since the COVID-19 outbreak, a gradual loosening of linguistic obligations in public institutions and governments has been observed in various jurisdictions in Canada. This article argues that in addition to legal requirements to provide minority language services, it is not justifiable for governments to suspend or curtail such services in an emergency situation, for reasons pertaining to public safety and public health. After performing a survey and analysis of government actions against their constitutional, legislative, and policy language obligations to highlight best practices and deficiencies, we discuss the policy implications of these actions. In conclusion, the article considers how governments could better uphold their language obligations in times of emergency.

Ma santé, ta santé, notre santé. Étude sur la santé mentale et les comportements à risque des jeunes adultes dans cinq universités au coeur du Canada - de Moissac, Danielle; Gueye, Ndeye Rokhaya; Rocque, Rhéa (Consortium national de formation en santé, Université de Saint-Boniface, 2019)
La transition de l’adolescence à la vie adulte constitue une des plus importantes transitions de la vie. À ce stade, le jeune doit développer des habiletés pour être en mesure de se prendre en charge et gérer ses responsabilités académiques et financières tout en maintenant un mode de vie sain. Des études démontrent que des perturbations à ce stade de vie peuvent avoir des conséquences importantes sur la santé psychologique et l’adaptation au changement, et qu’une instabilité émotionnelle peut avoir des retombées sur la performance et le fonctionnement psychosocial. Le milieu universitaire occupe une place privilégiée en tant que lieu d’intervention pour la promotion de la santé pour ces jeunes en raison du contact direct avec les étudiants au cours de plusieurs années. Une stratégie en matière de santé mentale, développée par la Commission de la santé mentale du Canada, souligne que les efforts de promotion en santé mentale et de prévention des troubles mentaux seront plus efficaces si les axes suivants sont respectés 1) savoir à qui s’adresser; 2) renforcer les éléments de protection et réduire les facteurs de risque; 3) fixer des buts clairs; 4) donner aux collectivités ce dont elles ont besoin pour agir; et 5) planifier pour le long terme. Ce projet de recherche s’inspire de cette stratégie : notre but à long terme est de favoriser le bien-être des jeunes adultes qui fréquentent un établissement universitaire en développant un outil de dépistage et des initiatives d’appui soutenables sur le campus et dans la communauté, selon les ressources disponibles. Pour ce faire, nous devons d’abord prendre connaissance de l’état de santé mentale de la population étudiante et des facteurs de risques et de protection qui leur sont propres. Ainsi, les efforts de prévention seront plus efficaces puisqu’ils seront conçus en fonction des besoins de la population cible et en consultation avec cette dernière. Cette étude a été menée dans cinq universités dans trois provinces, soit le Manitoba, l’Ontario et le Québec, dans le but de mieux comprendre l’effet du contexte linguistique sur la santé mentale et les comportements à risque des jeunes universitaires. Les cinq établissements choisis sont principalement des petites universités en contexte linguistique majoritaire (Brandon University et Université du Québec en Abitibi-Témiscamingue) ou minoritaire (Université de Saint-Boniface et Université Bishop’s). De plus, des participants de l’unique université bilingue du pays (Université d’Ottawa) ont participé. Ainsi, nous serons en mesure d’analyser les données en fonction de divers facteurs déterminants, dont le milieu linguistique dans lequel évolue l’étudiant. L’objectif principal de l’étude est de prendre connaissance de l’état de santé mentale et des comportements à risque prédominants des jeunes universitaires en contextes linguistiques majoritaires et minoritaires au Canada et d’identifier les facteurs de protection et de risque associés à leur bien-être. Notre but ultime est d’appuyer les étudiants, particulièrement ceux dans le besoin, dans leur atteinte d’une réussite académique. Ce rapport est descriptif : il présente les données générales se rapportant aux profils sociodémographique et ethnolinguistique, à l’état de santé mentale et aux comportements associés à cet état, ainsi qu’à la sécurité routière, au taxage et au harcèlement sexuel, aux pratiques sexuelles, à la consommation d’alcool, de drogues et de tabac, et à l’usage des nouvelles technologies; le tout, selon le genre et pour chacun des établissements d’enseignement postsecondaire. Un sondage a été distribué, sur papier ou en ligne, en fin novembre 2018 et en février 2019; au total, 2075 étudiants ont participé. Des analyses statistiques de fréquences et de proportions, selon le genre, ont été utilisées pour décrire les participants et leurs comportements.
fs-ref-orig: de Moissac, D., Gueye, N. R. et Rocque, R. (2019). Ma santé, ta santé, notre santé. Étude sur la santé mentale et les comportements à risque des jeunes adultes dans cinq universités au coeur du Canada. Consortium national de formation en santé, Université de Saint-Boniface et Université du Québec en Abitibi-Témiscamingue. fs-code-orig: de Moissac-2019b

My Health, your health, our health. A study on mental health and risk-taking behaviors of young adults on five university campuses in the heart of Canada - de Moissac, Danielle; Gueye, Ndeye Rokhaya; Rocque, Rhéa (Consortium national de formation en santé, Université de Saint-Boniface, 2019)
The transition from adolescence to adulthood is a time of dramatic change in one’s life. At this stage, youth are developing skills to be able to support themselves and manage academic and financial responsibilities, while maintaining a healthy lifestyle. Studies have shown that disturbances at this stage may have a strong impact on one’s psychological health and ability to adapt to change; emotional instability may have repercussions on performance and psychosocial functioning. Due to direct contact with young adults, postsecondary institutions are priviledged settings for health promotion activities. A mental health strategy developed by the Mental Health Commission of Canada suggests that to successfully promote health, and treat and prevent mental health issues, the following should be considered: 1) know who to reach; 2) strengthen protective factors and reduce risk factors; 3) set clear goals; 4) give communities what they need to take action; and 5) plan for the long term. This research project builds on this strategy. Our long term goal is to promote the well-being of university students by developing a screening tool and developing sustainable initiatives on campus and within the community, taking into consideration available resources. As such, we must first gain insight into the mental health status of the student population, including the risk and protective factors specific to these students. Thus, health promotion efforts will be more efficient, as they will have been created according to student needs and in consultation with this population. This study was conducted in five universities in three provinces, Manitoba, Ontario and Quebec, to gain insight into the impact of the linguistic context on mental health and risk-taking behaviors of students. The five participating universities were chosen mainly because of their small size and linguistic environment: Brandon University and the Université du Québec en Abitibi-Témiscamingue are in linguistic majority settings, whereas the Université de Saint-Boniface and Bishop’s University are in linguistic minority communities. In addition, participants were recruited from the only bilingual university in the country (University of Ottawa). Thus, data will be analysed according to various influencing factors, including the linguistic environment. The main objective of this study is to gain insight into the mental health status and predominant risk behaviors of university students in both majority and minority linguistic settings in Canada and to identify protective and risk factors relative to their well-being. The ultimate goal is to help those in need achieve academic success. This report is descriptive: it presents general data related to sociodemographic and ethnolinguistic profiles, mental health and related behaviors, road safety, bullying and sexual harassment, sexual practices, alcohol, drug and tobacco use and use of new technologies, according to gender, for each of the postsecondary institutions. A survey was conducted online or in print form at the end of November 2018 and in February 2019. In total, 2075 students participated. Statistical analysis of frequencies and proportions according to gender were used to describe participants and their behaviors
fs-ref-orig: de Moissac, D., Gueye, N. R., & Rocque, R. (2019). My Health, your health, our health. A study on mental health and risk-taking behaviors of young adults on five university campuses in the heart of Canada. Consortium national de formation en santé, Université de Saint-Boniface et Université du Québec en Abitibi-Témiscamingue. fs-code-orig: de Moissac-2019c

Workforce utilization of visible and linguistic minorities in Canadian nursing - Premji, Stephanie; Etowa, Josephine. B. (Journal of Nursing Management, 2012)
Background There is ample evidence of ethnic and linguistic segregation in the Canadian labour market. However, it is unknown if there is equitable representation of visible and linguistic minorities in nursing professions. Methods We cross-tabulated aggregate data from Statistics Canada’s 2006 Census. Analyses examined the distribution of visible and linguistic minorities, including visible minority sub-groups, among health managers, head nurses, registered nurses, licensed nurses and nurse aides for Canada and major cities as well as by gender. Results In Canada and its major cities, a pyramidal structure was found whereby visible and linguistic minorities, women in particular, were under-represented in managerial positions and over-represented in lower ranking positions. Blacks and Filipinos were generally well represented across nursing professions; however, other visible minority sub-groups lacked representation. Conclusions Diversity initiatives at all levels can play a role in promoting better access to and quality of care for minority populations through the increased cultural and linguistic competence of care providers and organizations.

Prolonged Impact of the COVID-19 Pandemic on the Well-being and Roles of Family/Friend Caregivers of Older Adults Living at Home in Canadian Official Language Minority or Majority Communities - Savard, Jacinthe; Savard, Sébastien; Duong, Patrick; Hatungimana, Nelly Oriane; Benoit, Josée; De Moissac, Danielle; Dupuis-Blanchard, Suzanne; Robitaille, Annie (Canadian Journal on Aging / La Revue canadienne du vieillissement, 2026)
Résumé Contexte. Des études menées pendant la pandémie de COVID-19 soulignent que le confinement a réduit l’accès aux services et accru les responsabilités et l’isolement des proches aidants. Objectif. Cette étude examine les répercussions à long terme chez 83 proches aidants de personnes âgées provenant de quatre provinces canadiennes. Méthodes. Les participants ont rempli un questionnaire en ligne entre octobre 2021 et février 2022, puis à nouveau six mois plus tard, sur l’aide fournie, le soutien reçu, la langue des services et le bien-être psychologique. De plus, huit aidants ont participé à une entrevue qualitative. Résultats. La plupart des services d’aide à domicile ont été maintenus pendant la pandémie, certains avec un personnel réduit, à l’exception des services de répit et de transport. Les aidants ont accru leur aide pendant les confinements, et cette implication accrue s’est poursuivie en 2022. Ils ont perçu un impact négatif de la pandémie sur leur santé et celle de la personne aidée. Les participants issus de communautés linguistiques minoritaires officielles ont décrit des difficultés supplémentaires pour accéder aux services dans leur langue préférée. Discussion. Une meilleure reconnaissance des besoins des aidants contribuera à soutenir leur rôle en tant que partenaires au sein des organismes de santé. Abstract Background. Studies conducted during the COVID-19 pandemic highlighted that confinement reduced access to services and increased caregivers’ responsibilities and isolation. Objectives. This study examines the longer-term impacts among 83 unpaid caregivers of older adults from four Canadian provinces. Methods. Participants completed an online questionnaire between October 2021 and February 2022, and again 6 months later, on the assistance provided, support received, language of services, and psychological well-being. Additionally, eight caregivers participated in a qualitative interview. Findings. Most home support services were maintained during the pandemic – some with restricted staffing – except for respite and transportation services. Caregivers increased their assistance during the lockdowns, and this higher involvement persisted in 2022. They perceived a negative impact of the pandemic on their health and that of the care recipient. Participants from official language minority communities described additional challenges accessing services in their preferred language. Discussion. Greater recognition of caregivers’ needs will help support their role as partners within health organizations.

Regards croisés Ontario-Québec : les services de soins de santé mentale des communautés de langue officielle en situation minoritaire de 1950 à nos jours - Thifault, Marie-Claude; Lebel, Marie; Perreault, Isabelle; Desmeules, Martin (Reflets, 2012)
Considérant qu’un Canadien sur neuf hospitalisé pour maladie mentale retournera à l’urgence moins d’un mois après sa sortie d’hôpital, il importe de documenter, dans une perspective socio-historique, les itinéraires « transinstitutionnels » des personnes souffrant de troubles psychiques. Nous proposons ici une note de recherche sur l’enquête que nous menons sur l’évolution des services de soins de santé mentale des communautés de langue officielle en situation minoritaire, en particulier, les communautés francophones de l’Est et du Nord ontarien ainsi que de la communauté anglophone de l’Ouest du Québec. Ces regards croisés entre deux régions francophones de l’Ontario et le Montréal anglophone visent une meilleure compréhension de l’impact des facteurs de « langue de service » et de « culture » sur la santé mentale des communautés francophones en situation minoritaire (CFSM). Mots-clés : services de santé mentale, désinstitutionnalisation, minorités linguistiques, Ontario, Québec